Vital Registration System in Nepal - Mulmi, Sudan Kumar (Kalika Journal of Multidisciplinary Studies, 2021)
The events which are occurring in our life cycle such as birth, death, marriage, divorce and internal migration are the vital events. The vital event registration system is the dynamic study of population changes and it provides the legitimacy of each incident of each individual. Vital statistics generated through civil registration systems are the major source of continuous monitoring of birth, death, marriage, divorce and internal migration over time. The main objective of this study is to find out the annual trend of registration of vital events like birth, death, marriage, divorce and internal migration in Nepal as well as to highlight the need for investment in better registration of all vital events. This article is based on secondary data of nationwide annual vital events statistics obtained from ministry of local development. The number of birth registration has been increased by 2164.39, death by 2301.26, marriage by 3490.75, divorce by 67.09 and internal migration by 2683.68 in each year than preceding year. The registration of all vital events shows the rising trend in Nepal. As many Nepalese are not registering the vital events immediately so concern authorities should come with effective awareness plan to make people aware of importance of registration of vital events in their life as well as to nation.